Clinical Outcome of Silent Subtype III Pituitary Adenomas Diagnosed by Immunohistochemistry. Issue 12 (December 2015) - Richardson, Timothy E.; Mathis, Derek A.; Mickey, Bruce E.; Raisanen, Jack M.; Burns, Dennis K.; White, Charles L.; Hatanpaa, Kimmo J.
Abstract : Abstract: Silent subtype III pituitary adenomas (SS-3) are nonfunctioning radiosensitive adenomas that may be associated with an increased risk of recurrence and invasion. The features that have been proposed to be diagnostically important are identifiable by electron microscopy (EM) and include an enlarged Golgi apparatus, along with several other ultrastructural features. The often limited availability of EM and the uncertainty about the relative importance of individual features pose practical challenges to the diagnosis. We hypothesized that it may be possible to diagnose SS-3 based solely on a markedly enlarged Golgi apparatus identified at the light microscopic level. In this prospective study, we used immunohistochemistry (IHC) for the Golgi apparatus with the MG-160/GLG-1 antibody to identify 10 cases with features suggestive of SS-3. Electron microscopy was performed for confirmation on 1 case. Compared with a control group of 20 conventional null cell adenomas, the SS-3 adenomas showed an increased MIB-1 proliferation index (p < 0.01), a higher risk of invasion (p < 0.01), and a higher incidence of recurrence (p < 0.01). Thus, in this first controlled study, we demonstrate that SS-3 is clinically aggressive and identifiable by IHC, without the need for EM. The routine diagnostic workup of nonsecreting adenomas should rule out SS-3, which can be done quickly and efficiently by IHC. Abstract : Supplemental digital content is available in the text.